Specyfika pracy socjalnej w dobie pandemii. Badania jakościowe wśród pracowników pomocy społecznej - Zaborowska, Agnieszka; Szyszka, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article presents the results of qualitative research carried out at the Institute of Sociological Sciences of the John Paul II Catholic University of Lublin concerning the work experience of employees of the social welfare system related to the COVID-19 pandemic. The research was conducted in September-November 2021 among social workers and family assistants from the Lubelskie Voivodeship. The research was carried out using the technique of individual in-depth interviews. The obtained data complement the current research on social welfare institutions and their employees operating during the COVID-19 pandemic. The article presents the opinions of social workers on changes in working conditions, as well as observations on the consequences of the pandemic in contacts with clients.